2020
DOI: 10.1007/s13197-020-04551-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of added calcium and heat setting on gel forming and functional properties of Sardinella fimbriata surimi

Abstract: Present study evaluates the effect of calcium and heat setting on gel characteristics of lesser sardine (Sardinella fimbriata) surimi. Total seven formulations were made namely, S. fimbriata minced meat without heat setting (A1), minced meat with heat setting (A2), S. fimbriata surimi control (without addition of calcium) without heat setting (B1), control (without addition of calcium) with heat setting (B2), surimi added with 0.3% calcium without heat setting (C1) and surimi added with calcium with heat setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Gel properties can be improved by optimizing setting, mediated by endogenous TGase [ 7 ]. Calcium ions have been implemented to enhance TGase activity, leading to higher protein cross-linking via non-disulfide covalent bonds [ 8 ]. Plant phenolics [ 9 , 10 ] or cross-linking enzymes e.g., microbial TGase [ 11 , 12 ] or chitooligosaccharide [ 13 , 14 ] have been used in surimi.…”
Section: Introductionmentioning
confidence: 99%
“…Gel properties can be improved by optimizing setting, mediated by endogenous TGase [ 7 ]. Calcium ions have been implemented to enhance TGase activity, leading to higher protein cross-linking via non-disulfide covalent bonds [ 8 ]. Plant phenolics [ 9 , 10 ] or cross-linking enzymes e.g., microbial TGase [ 11 , 12 ] or chitooligosaccharide [ 13 , 14 ] have been used in surimi.…”
Section: Introductionmentioning
confidence: 99%
“…Free iron may operate as a prooxidant, speeding up the oxidation of lipids. Lower TBARS levels may be obtained as a result of removing lipids and oxidative constituents from mince [56]. In general, lipid and myoglobin oxidation in fish muscle occurred at the same time, and one process seemed to promote the other [22,25].…”
Section: Lipid Oxidation and Fishy Odormentioning
confidence: 95%
“…The incorporation of various additive ingredients was recently reported on surimi gel, i.e., protein hydrolysate [9,10], inulin [11], transglutaminase [11,12], sodium bicarbonate [13], Micro-algae [14,15], hydrocolloids [16], fish oils [17], coconut husk extract [12,18], cellulose nanofibrils [1], fibers [3,[19][20][21], fatty acid [22], camel milk [23], vegetable oils [24] and amino acids [5]. Some other studies have reported on the addition of calcium from fish bone for textural improvement of silver carp fish sausage [25] and sardine (sardinella fimbriata) surimi gel [26] under normal-salt condition. However, additive-protein interaction change as different calcium and fish species is formulated, particularly under reduced-salt condition.…”
Section: Introductionmentioning
confidence: 99%
“…This calcium-based material has the potential to increase the quality characteristics of the surimi-based product during the gel formation process through filling and inducing cross-linking principles [30]. Calcium addition was reported to increase the overall acceptability of surimi gel, with no effect on flavor [26]. The recommended dietary allowance (RDA) of calcium-based food fortification ranges from 0.4 to 2.5 g [30].…”
Section: Introductionmentioning
confidence: 99%